Investigation of Dynamic Friction Properties of a Dual Mass Flywheel for Commercial Vehicles - Karlsson, Johan (My University, 2018)
In order to meet new requirements on exhaust emissions the trend is to downsize and reduce the speed of conventional engines. This leads to larger vibrations levels transmitted to the rest of the powertrain and ultimately to the rest of the vehicle. One way of reducing the transmission of these vibrations is to use a dual mass flywheel. This is a common solution for passenger cars but not as well known for commercial vehicles. In this master thesis the dynamic friction properties of a dual mass flywheel for a heavy duty truck is analysed. The analysis involves both simulations and physical experiments. The aim is to investigate how the friction is depending on rotational speed and torque and how well the simulation model correlates with the measured values. The simulations were done in MATLAB with a linear spring damper model. The input to the model was a torque signal and the final output was the dynamic behaviour of the dual mass flywheel. The friction losses were then determined by analysing the input torque and the resulting movement of the dual mass flywheel. A test rig at AB Volvo’s site in Lundby was used for the measurements. A dual mass flywheel for a Volvo FH16 truck was rotated at different speed with different levels of torque amplitude. The speeds of the primary and secondary masses of the flywheel were measured along with the torque input to the system. The friction losses were then calculated by analysing the measured torque and movement of the dual mass flywheel. The results from the measurements indicate that the friction in the dual mass flywheel is primarily viscous. This means that the losses are dependent on the speed difference between the primary and secondary mass. No direct relation between the losses and the rotational speed could be found. The results show the same behaviour when the linear simulation model is used to calculate the losses. If the right value of the damping coefficient is used the results from the measurements and the simulations are similar. Keywords: Dual Mass Flywheel, DMF, Torsional Vibrations, Commercial Vehicles
Keywords: Transport; Teknisk mekanik; Transport; Applied Mechanics